L-histidine augments the response to 1-deamino-8-D-arginine vasopressin in Brattleboro homozygous (di/di) rats. - Charnogursky, G (1990)
Studies in vitro have shown that L-histidine increases the hydroosmotic response to vasopressin. We examined whether this phenomenon occurs also in vivo. Homozygous Brattleboro rats (di/di) were fed a regular diet (0.5% histidine) or a diet enriched with histidine and received 1 ng of 1-deamino-8-D-arginine vasopressin (dDAVP) daily. Addition of histidine (1% by weight) increased post-dDAVP urine osmolality to a level higher than that of control (502 +/- 62 vs. 316 +/- 36 mosmol/kg, P less than 0.05). Similar results were seen with 3.0% and 5.5% dietary histidine. There were significant increases in free-water reabsorption and in the ratio of free-water reabsorption to osmolar clearance, but no difference in osmolal clearance. No significant effect was found with supplemental histidine of 0.5% or less. The cause for these findings appears not to be the metabolism of histidine, since the nonmetabolizable D-histidine had a significant, albeit smaller, effect, and the isonitrogenous addition of albumin, alanine, arginine, or glutamine was ineffective. In part, histidine may operate by increasing cAMP since the renal cAMP content in response to vasopressin is increased in histidine-fed rats (13.1 +/- 0.9 vs. 9.8 +/- 0.8 nmol/g dry weight, P less than 0.01). The role of prostaglandins appears less clear. Histidine greatly decreased urinary PGE2 during baseline (1.5 +/- 0.3 vs. 7.0 +/- 2.3 micrograms/mg creatinine, P less than 0.001), but it profoundly augmented urinary prostaglandin excretion after dDAVP stimulation (40.0 +/- 4.2 vs. 7.0 +/- 2.0 micrograms/mg creatinine, P less than 0.001).